PENGARUH CUSTOMER INVOLVEMENT TERHADAP CO-CREATION VALUE DI INDUSTRI PERBANKAN DIGITAL DI INDONESIA - Rinaldi Bursan; Indah Listiana; Shinta Tantriadisti (Nusantara Hasana Journal, 2025)
This study examines the causal relationship between Customer Involvement, Co-Creation Value, Satisfaction, and Loyalty in the context of collaboration-based customer relationship management. The main objective of this study is to understand how customer involvement in the service process can influence perceptions of shared value, increase satisfaction, and ultimately form strong customer loyalty. The theoretical approach used refers to Service-Dominant Logic, which places customers as active partners in value creation, not just recipients of services. Through a quantitative approach and structural equation modeling, this study finds that customer involvement plays an important role in creating more relevant and meaningful experiences, which in turn have a positive impact on satisfaction and loyalty. The practical implications of the results of this study emphasize the importance of participatory and interactive strategies, including the use of digital technology, to increase customer engagement. By building a more inclusive and responsive service system, companies can create long-term, mutually beneficial relationships with customers and increase competitive advantage in the digital economy era.